Pengaruh Kepercayaan Masyarakat terhadap Pembiayaan Mudharabah di BSI Kecamatan Belo Kabupaten Bima - Nurunnasiah; Sabrang Gilang Gemilang; Muhammad Helmy Reza; Lalu Ahmad Ramadani (Jurnal Perbankan Syariah, 2025)
Trust is a person's willingness to rely on another person involved in an exchange because he or she believes in that person. Because trust is very important in the banking industry, customer trust in banks is an important component that influences customer loyalty. Although the majority of the people of Renda Village, Belo District, Bima Regency are Muslim, many people are less aware of Islamic Banking products, which causes them to have less trust in Islamic Bank services and products. In addition, the knowledge and understanding of the community indirectly affect their perspective on the perception of Islamic banking. This study uses a quantitative method, with a research population of 7000 and a sample of 100 respondents. In this study, statistical analysis was carried out using SPSS. The data analysis techniques used were validity and reliability tests, classical assumption tests, and simple linear regression tests. The results of this study indicate that there is a positive and significant influence of the level of public trust on mudharabah financing with a value of the T-test of the trust level variable of 5.702 with a significance of 0.000 <0.05. Variable X1 has a t-test of 5.702 with t-table = 1.985.